L’autonomie dans l’invisibilité. Les accompagnantes des élèves en situation de handicap - Christophe Chevalier; Arthur Imbert; Alicia Jacquot (La Nouvelle Revue du Travail)
The period since the 1980s has witnessed numerous educational professionals’ replacement by less qualified and lower paid technical workers hired to help manage student heterogeneity – an arrangement enabling the implementation of low-cost public policy. The trend is exemplified by special needs assistants responsible for disabled pupils’ overall inclusion. Despite the precarity of their situation, however, these actors have developed margins of autonomy in their daily work through the way they manage time, activities and crises. Undermining preconceived notions of the jobs they do, the article calls for a more granular analysis of the relationship between objective and subjective precariousness.